Plant Sources, Extraction Methods, and Uses of Squalene - M. Azalia Lozano-Grande; Shela Gorinstein; Eduardo Espitia-Rangel; Gloria Dávila-Ortiz; Alma Leticia Martínez-Ayala (International Journal of Agronomy, 2018)
Squalene (SQ) is a natural compound, a precursor of various hormones in animals and sterols in plants. It is considered a molecule with pharmacological, cosmetic, and nutritional potential. Scientific research has shown that SQ reduces skin damage by UV radiation, LDL levels, and cholesterol in the blood, prevents the suffering of cardiovascular diseases, and has antitumor and anticancer effects against ovarian, breast, lung, and colon cancer. The inclusion of SQ in the human diet is recommended without causing health risks; however, its intake is low due to the lack of natural sources of SQ and efficient extraction methods which limit its commercialization. Biotechnological advances have developed synthetic techniques to produce SQ; nevertheless, yields achieved are not sufficient for global demand for industrial or food supplement purposes. The effect on the human body is one of the scientific issues still to be addressed; few research studies have been developed with SQ from seed or vegetable sources to use it in the food sector even though squalene was discovered more than half a century ago. The aim of this review is to provide an overview of SQ to establish research focus with special reference to plant sources, extraction methods, and uses.